Saints of the Soil: Sufi–Bhakti Thought in Regional Folk Traditions - Ashwathamma K.; Syed Bilal I. (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
Saints of the Soil: Sufi-Bhakti Thought in Regional Folk Traditions examines the immanent presence of mystical spirituality in folk literature in India in terms of the works and traditions of Amir Khusro, Baba Bulleh Shah, Kabir Das, Meera Bai, Shishunala Shariff, and Peer Saheb Hyderabadi. The Sufi and Bhakti poems written in the regional language had formed a people’s philosophy that opposed dogmatic faiths, caste distinction, and authority in general. This paper investigates the way in which these Sufi-Bhakti poet-saints have been able to articulate metaphysical ideas of ishq, bhakti or divine love, realization of the Self, and spiritual equality in terms of folk idioms and folk songs for mass audiences. The Hindavi poems of Amir Khusro, Punjabi kaafis of Baba Bulleh Shah, dohe of Kabir Das, devotional melodies of Meera Bai, Kannada vacanas of Shishunala Shariff, folk poems of Shishunala Shariff, and Deccani Urdu kalams of Peer Saheb Hyderabadi demonstrate that these poets were inspired by a shared normative principle of Sufi-Bhakti philosophy that transcends communal, sectarian, and religious boundaries.